Citizen Involvement in the Formulation of Public Policy - Molokwane, T. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
To assist the government in determining its mandate, citizens should be involved as they best know their needs. The significance of citizen engagement in the process of policy formulation is rooted in among others, the fact that public policy outputs and effects affect those to whom the policy is targeted at. This paper identifies areas of contribution of citizen involvement in public policy formulation. Literature illustrates that some governments do not engage citizens sufficiently in the process of public policy formulation. It remains relatively unclear as to why government evades engaging citizens in the formulation of public policy and conduct random and cursory consultations in order to enshroud the lack of consultation. The case of Botswana, illustrates that citizens made adequate efforts in the contribution to the formulation of the country’s public policy. This study therefore, shows that citizens are an important stakeholder hence government engages them in a specific domain. This study also discusses selected cases of citizen engagement in Botswana. The study further acknowledges that the failure of policy implementation can be linked to failure on the part of civil servants where they do not follow proper procedure as recommended by the government. To this end, public policy successes require strong involvement of public officials to avoid any policy implementation failure.
Journal article published in the International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Citizen Involvement; New Public Management; Public Policy; Public policy; Public administration -- Citizen participation